Un archivio in frammenti. Ripensare i “papiri di Ravenna” (secoli v-ix) - Internullo, Dario (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2024)
Abstract An Archive in Fragments: Rethinking the ‘Ravenna papyri’ The main purpose of this essay is to describe and present an up-to-date picture of the current state of knowledge concerning the ‘Ravenna papyri’. This corpus, well known to many historians of Late Antiquity, runs by several interpretations between studies regarding its precise numerical, chronological, and typological definition. With the intention of recalibrating and thus consolidating this definition, the perspective adopted here is an archival one: the survey and analysis have included all the documents, written mainly (but not exclusively) on papyrus between the 5th and the mid-9th centuries, which have reached us through the archives of the archbishops of Ravenna. The work takes into account not only the original papyrus documents, but also those that have come down to us through later parchment copies. It also includes the numerous documents that have been transcribed, summarized, or simply mentioned in two sources that have hitherto been little used in discussions of the ‘Ravenna papyri’: Agnellus’ Liber Pontificalis (9th century) and the Breviarium Ecclesiae Ravennatis (10th century). Reconstructed in this way, the corpus, consisting of 133 items and enclosing what we know of a large late antique and early medieval archive, offers new research insights and reveals itself as a historical source worthy of investigation. In this regard, the last part of the work also investigates the possible moments that led to the creation and changes of this archive, distinguishing between a slower ‘time of pious donations’ and a more accelerated ‘time of imperial privileges’, the latter being responsible for a real change of course in the history of the archive in the late 6th century. Finally, the discourse is completed by an appendix with a descriptive list of all the items that make up the corpus.